2021
DOI: 10.1002/jctb.6738
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with copper‐loaded chitosan nanoparticles promotes early growth and enzymatic antioxidant defense of maize (Zea mays L.) seedlings

Abstract: BACKGROUND:The unique features of nanoparticles can improve the effectiveness of seed priming with metallic ions, boosting plant growth and the defense response. The current study aimed to evaluate the effects of nanopriming of maize (Zea mays L.) seeds with chitosan nanoparticles containing copper ions (NPCu) on the growth and photosynthetic activity of non-stressed seedlings, as well as on the germination and antioxidant response of seeds undergoing deterioration caused by high relative humidity and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The glassy state raises the viscosity of the intracellular fluid and decreases metabolic activity in the cytoplasm [ 85 ]. Further seed longevity of L. royleana than that in L. iberica may be due to less oil in L. royleana seeds [ 86 ]. Hence, it can be inferred, high saturated fatty acids during seed storage induce a decline in the lipid fluidity of cell membranes and a rise in MDA and ROS accumulation [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The glassy state raises the viscosity of the intracellular fluid and decreases metabolic activity in the cytoplasm [ 85 ]. Further seed longevity of L. royleana than that in L. iberica may be due to less oil in L. royleana seeds [ 86 ]. Hence, it can be inferred, high saturated fatty acids during seed storage induce a decline in the lipid fluidity of cell membranes and a rise in MDA and ROS accumulation [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the effects induced by NMs per se , some types of NMs (such as polymeric NPs) can be used as efficient carrier systems for bioactive molecules (e.g. plant growth regulators and metallic ions), which further regulate specific processes in germination ( Pereira et al , 2017 ; Gomes et al , 2021 ). The beneficial effects triggered by NMs or molecules released by them are not restricted to germination, as improved seedling growth and stress resistance are observed, which can result in higher productivity ( Pereira et al, 2019 , 2021 ; Shelar et al , 2021 ; Nile et al , 2022 ).…”
Section: Nms Affect Plants At the Organ And Organism Levelsmentioning
confidence: 99%
“…Apart from the delivery of plant growth promoters, biopolymeric nanoparticles have also been shown to have growth-promoting properties. Several studies have shown that chitosan nanoparticles promote seed germination in crops and can therefore be used to produce healthy seedlings [ 148 , 149 , 150 ].…”
Section: Main Applications Of Biodegradable Polymeric Nanoparticlesmentioning
confidence: 99%